Decolonizing the Mind: The politics of survival in Sinan Antoon’s The Corpse Washer (2013) - Aziz, Ahmed Saad (Research Journal in Advanced Humanities, 2026)
This study traces the intersection of trauma, war, and the politics of survival in post-war Iraqi fiction through a keen critical analysis of Sinan Antoon’s masterpiece, The Corpse Washer (2013). The study examines how prolonged violence, foreign occupation, sectarian war, and political instability influence both individual subjectivity and social memory in contemporary Iraqi landscape, situating the novel within postcolonial and trauma theory frameworks. The study explores how the novel challenges prevailing imperial trajectories and narratives Iraqi lived experience through intimate storytelling, drawing on theories of decolonization, especially Ngũgĩ wa Thiong’o’s idea of “decolonizing the mind.” The novel illustrates how individual and collective identities are fragmented under implications of occupation and systemic ruin through the protagonist Jawad, an aspiring sculptor forced by fate to take on his father’s skill of washing the corpses. A sheer crisis of self in a culture where death consistently eclipses art, beauty, and normalcy is reflected in Jawad’s internal struggle. The study argues that this conflict between ceremonial work and creative desire represents the fight to protect humanity in the face of dehumanizing mechanism. Through the lens of Ngũgĩ Thiongʼo’s theory of decolonization, Antoon’s novel offers a significant contribution to decolonization of the mind as a “writing history back” narrative that challenge dominant western mindset of Iraq as solely site of war, violence, and radical thoughts. Through the multifaceted figure of Jawad, the protagonist, who works as corpse’s washer, Antoon asserts Iraqi subjectivity, showing a deeply human outlook on trauma, chaos, and survival.